Nonfat dry milk in longanisa - Edralin, Christina R.; Guzman, Matilde P. (1966.)
The role of nonfat dry milk in native pork sausage of longanisa was investigated. Nonfat dry milk was used as binder and filler which improves slicing and binding properties, increase bulk of sausage, and increase the protein content. The first phase of the experiment consisted of acceptability tests of four experimental sausages made with 45, 55, 65, and 75% nonfat dry milk based on the weight of the lean meat. The second phase involved the objective and organoleptic evaluation of the two highest levels of nonfat dry milk||: 65 and 75%. Shrinkage determination and protein analyses were done with the sausage containing 75% nonfat dry milk. The results of the study suggest the manufacture of improved sausages with 75% nonfat dry milk.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Milk, Nonfat; Sausages